Case Report: Dysfunction of the Paraventricular Hypothalamic Nucleus Area Induces Hypersomnia in Patients - Wang, Zan; Zhong, Yu-Heng; Jiang, Shan; Qu, Wei-Min; Huang, Zhi-Li; Chen, Chang-Rui (Frontiers in Neuroscience, 2022)
Background: Hypersomnia is a common and highly impairing symptom marked by pathological excessive sleepiness, which induces suboptimal functioning and poor quality of life. Hypersomnia can be both a primary (e.g., hypersomnolence disorder) and secondary (e.g., tumors, and head trauma) symptom of disorders. However, its underlying mechanisms remain largely unknown. Case presentation: We report that three clinical cases with lesions around the paraventricular nucleus of the hypothalamus (PVH) showed excessive daytime sleepiness and a prolonged nocturnal sleep lasting more than 20 h per day. Sleep architecture and subjective daytime sleepiness were examined by polysomnography. These cases were presented with stroke, myelin oligodendrocyte glycoprotein antibody associated disorders and neuromyelitis optical spectrum disorder, respectively. Magnetic resonance imaging showed lesions around the paraventricular nucleus area of the hypothalamus (PVH) area in all these three patients. After treatment of their primary disorders, their excessive sleep decreased as the PVH area recovered. Conclusion: Our findings suggest that the PVH may play an essential role in the occurrence of hypersomnia.